MEMBANGUN KEMBALI JEMBATANANTARA KREATIVITAS DAN PENDIDIKAN JASMANI - Hari Amirullah Rachman (Jurnal Pendidikan Jasmani Indonesia, 2006)
Every child is born with creative potential, but this potential may be stifled if care is not takento nurture and stimulate creativity. Creativity is the ability to see things in a new and unusuallight, to see problems that no one else may even realize exist, and then come up with new,unusual, and effective solutions to these problems. Children like to try out different ways,experiment with different materials, and see what they can do creatively. Finding differentways to exspressing themselves physically satisfies the urge for creative action. But it mustbe their ways, their ides, and their accomplishment.Physical education gives childrenopportunity for exploratory and creative activity. Children need an opportunity to tray outtheir own ideas, solve some of their own movement problems and bring forth movement oftheir own origin. Teachers need to take advantage of this drive by providing opportunity forthe child to come up with his own movement ideas.Key words: creativity, physical education